Literatur review: Faktor penyebab rendahnya cakupan inisiasi menyusu dini dan pemberian ASI eksklusif - Haripin Togap Sinaga; Marni Siregar (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
Globally the coverage of early initiation breastfeeding (EIBF) and exclusive breastfeeding (EBF) still low. In Indonesia, the coverage of EIBF and exclusive breastfeeding was 52,8% and 37,3%. This study aimed to review what factors affected the target of EIBF and EBF. Method, the study was a literature review. Eleven scientific articles were critically reviewed based on objectives, methods, and results presented in the articles. The articles were written by Indonesian authors and published in indexed journals during the year 2015 to 2020. Three databases were used; SINTA, Google Scholar, and National Library to search the articles using keywords “Early Initiation Breastfeeding and Exclusive breastfeeding” Data were analyzed with the qualitative method by presenting a summary, compare and contrasting, and critics and opinion. Results, of eleven articles, three were qualitative studies with total respondents 22, 28, and 81 mothers and eight quantitative studies range respondent from 110 mothers to 300.000 household mothers. There were six factors affecting EIBF and EBF coverage; 1) implementation of government regulation, 2) family support, 3) maternal education and occupation, 4) breastfeeding counseling, 5) pre-term babies and 6) local culture. In conclusion, the main factors causing the low coverage of EIBF and EBF are government commitment, family support, mother's education and occupation, inactive breastfeeding counseling, babies born at term, and cultural factors.